Społeczeństwo zrównoważone jako sposób podnoszenia jakości życia - Mroczko, Franciszek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Adopting economic development and requirements of environmental protection seems to be the main idea of level-headed development. The realization of level-headed strategy of development leads to the structure of level-headed society. The author has performed in Poland a review of features of level-headed society structure as a factor of improving the quality of life. The author has particularly taken a stand in such features as creation of postindustrial society, level of GDP, education, condition of natural environment, circulation, equality of rights, level of corruption, quality of social custody and medical care, level of informatization and sense of safety of citizens. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 217-228